2014
DOI: 10.3109/03008207.2014.904856
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix sub-types and mechanical stretch impact human cardiac fibroblast responses to transforming growth factor beta

Abstract: Understanding the impact of extracellular matrix sub-types and mechanical stretch on cardiac fibroblast activity is required to help unravel the pathophysiology of myocardial fibrotic diseases. Therefore, the purpose of this study was to investigate pro-fibrotic responses of primary human cardiac fibroblast cells exposed to different extracellular matrix components, including collagen sub-types I, III, IV, VI and laminin. The impact of mechanical cyclical stretch and treatment with transforming growth factor b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Altered mechanical properties of the heart occurs early in many types of cardiac disease [17]. Thus, in addition to increased neurohormonal activity [18,19] and sterile inflammation [20,21] that are well-known to increase ECM production, mechanical factors are crucial for the development of fibrosis.…”
Section: Cardiac Fibrosis and Heart Diseasementioning
confidence: 99%
“…Altered mechanical properties of the heart occurs early in many types of cardiac disease [17]. Thus, in addition to increased neurohormonal activity [18,19] and sterile inflammation [20,21] that are well-known to increase ECM production, mechanical factors are crucial for the development of fibrosis.…”
Section: Cardiac Fibrosis and Heart Diseasementioning
confidence: 99%
“…The defining marker of fully differentiated myofibroblasts in research and clinical diagnostics is the relatively high expression of ␣-SMA (not expressed by protomyofibroblasts) that incorporates into a prominent stress fiber network underlying their contractile function (17). The expression of ␣-SMA can be determined using molecularbased (e.g., quantitative real-time polymerase chain reaction method) or protein-based (e.g., immunofluorescence staining or Western blot analysis) assays (25,99,100). Contractile activity of myofibroblasts can be detected by measuring their ability to contract a collagen gel (18).…”
Section: Important Parameters For Cardiac Myofibroblast Differentiatimentioning
confidence: 99%
“…However, these studies provide useful information for investigating the roles of mechanical cues in regulating cardiac myofibroblast differentiation. Notably, only studies within the last 5 years focused on the mechanism for mechanoregulation of cardiac myofibroblast differentiation (13,85,99,100).…”
Section: Effect Of Ecm Stiffness On Cardiac Myofibroblastmentioning
confidence: 99%
“…Our theoretical agent-based model simulations predicted that strain-induced collagen damage combined with strain-induced increases in collagen production can indeed give rise to divergence – i.e., a strain regime where increased strains yield increased content but decreased alignment – but only if there is a very sharp transition from low to high collagen deposition rates at exactly the right strain value. Experimental evidence strongly supports the idea that strain or load can modulate collagen synthesis: in vitro measurements of strain-dependent collagen deposition by fibroblasts typically show increases on the order of 2-fold from unloaded to highly loaded constructs (Butt and Bishop 1997; Lee et al 1999; Papakrivopoulou et al 2004; Atance et al 2004; Husse et al 2007; Balestrini and Billiar 2009; Guo et al 2013; Watson et al 2014), while increased loading of healing tendons in vivo (exercise vs. complete unloading) gives rise to ∼3-fold increases in matrix content (Thomopoulos et al 2003; Galatz et al 2009). However, it is less clear to what extent fiber damage actually occurs in the healing supraspinatus tendons that motivated our model (Thomopoulos et al 2003; Galatz et al 2006, 2009).…”
Section: Discussionmentioning
confidence: 78%
“…10, wherein collagen expression doubles from no strain to 10% strain. This assumption was based on previous experimental reports that measured collagen I and collagen III expression after subjecting fibroblasts to various strain levels in vitro (Carver et al 1991; Butt and Bishop 1997; Parsons et al 1999; Lee et al 1999; Breen 2000; Kim et al 2002; He et al 2004; Atance et al 2004; Yang et al 2004; Loesberg et al 2005; Shalaw et al 2006; Husse et al 2007; Tetsunaga et al 2009; Kanazawa et al 2009; Blaauboer et al 2011; Miyake et al 2011; Galie et al 2011; Petersen et al 2012; Huang et al 2013; Watson et al 2014; Liu et al 2016; Manuyakorn et al 2016; Jiang et al 2016). The vast majority of these studies observed that collagen levels were increased ≤ 2-fold.…”
Section: Methodsmentioning
confidence: 99%